Sedimentation in Ice-Damned Glacial Lake Assiniboine, Saskatchewan, and Catastrophic Drainage Down the Assiniboine Valley - Wolfe, Brent; Teller, James (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTIce-dammed glacial Lake Assiniboine covered approximately 1500 km2 in eastern Saskatchewan at about 11,000 BP. Lithofacies in two cores from the lake basin were identified, correlated, and linked to paleolake strandlines and inflow and outflow channels discerned from aerial photos and surface mapping. Deeper lake stages are reflected by silt and clay varve deposition in the deepest part of the basin, whereas shallower stages are represented by fluctuating grain size and current-generated sedimentary structures in sediments nearer to where influxes of melt-water occurred. The stratigraphie record revealed six lake phases, beginning with a shallow period when water collected in the interlobate area between ice on the Duck Mountain Upland to the east and the Assiniboine Ice Lobe to the west. A rise in lake level to about 495 m occurred as the southern outlet was dammed by ice. After about 85 varve years, waters from the Porcupine Hills Upland to the north flooded into glacial Lake Assiniboine, perhaps as a result of the drainage of an ice marginal lake, causing erosion at the lake's southern outlet and a drop in lake level. A second major influx of water from the Porcupine Hills area, at least 20 varve years later, led to downcutting of the outlet and draining of Lake Assiniboine. Shallow and deep channels, streamlined hills, and scattered boulders adjacent to the now-entrenched Assiniboine valley at the former outlet of glacial Lake Assiniboine suggest that the lake drained catastrophically. Similar geomorphic features at sites downstream along the Assiniboine valley are also indicative of catastrophic flow, although only those areas north of the Qu'Appelle River spillway junction are predominantly attributed to outbursts from glacial Lake Assiniboine.